Images of the future city time and space for sustainable development - Höjer, Mattias 1966-; Gullberg, Anders 1947-.; Pettersson, Ronny; Ahlroth, Sofia; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
The future Western city look like if energy use per capita was reduced by sixty percent? This is the overarching question researchers have addressed in a major backcasting study carried out in Stockholm in recent years, and their answers are revealed in this book. In Images of the Future City: Time and Space For Sustainable Development, fourteen researchers from numerous disciplines offer details on a variety of aspects of a future sustainable city, including travel, housing, eating, time use, consumption and urban form. The result is a complete illustration of what it could be like to live in a city based on sustainable energy use, with Stockholm 2050 as the geographical and temporal setting. This book is an ideal complement to studies showing the potentially devastating ecological effects of climate change, studies trying to calculate the costs of climate change, and studies trying to identify the most pressing needs in preparing for the new climate. In Images of the Future City: Time and Space For Sustainable Development, fourteen researchers from numerous disciplines offer details on a variety of aspects of a future sustainable city, including travel, housing, eating, time use, consumption and urban form. The result is a complete illustration of what it could be like to live in a city based on sustainable energy use, with Stockholm 2050 as the geographical and temporal setting. This book is an ideal complement to studies showing the potentially devastating ecological effects of climate change, studies trying to calculate the costs of climate change, and studies trying to identify the most pressing needs in preparing for the new climate.
1. The Sustainable City -- 2. Limitations and Necessities -- 3. Limits of Urban Sustainability -- 4. Urban Tempo and Structure -- 5. Introduction - Urban Structure, Activity Patterns and Technology -- 6. Development of Urban Structures -- 7. Visions and Urban Structures -- 8. Stockholm?s Urban Development -- 9. Future Cities ? Possible Changes -- 10. Time and Consumption -- 11. Housing and Other Premises -- 12. Food -- 13. Travel -- 14. Durable Goods -- 15. Time Use in the Future -- 16. Production -- 17. Vehicles -- 18. Housing -- 19. Summary of Technical Potential -- 20. Introduction -- 21. Six Images of the Future ? Introduction and Definitions -- 22. Urban Cores 2050 ? Fast and Slow -- 23. Suburban Centers ? Fast and Slow -- 24. Low-rise Settlements ? Fast and Slow -- 25. Measures and Possibilities in Concentration -- 26. Time Use Today and in Images of the Future -- 27. Energy Use From the Household Perspective -- 28. Energy Use in 2000 and 2050 -- 29. Suburban and Inner City Families with Children and No Car -- 30. Images of the Future From a National Economic Perspective -- 31. The Sustainable City: Necessary System Shifts and Their Conditions; Appendixes.
Electronic reproduction.
Keywords: Sustainable urban development; City planning; Electronic books